Effect of Plastic Crushing of the Car Body on Optimization of Rheological Properties of Safety Belts - Trojnacki, A.; Życzkowski, M. (Engineering Transactions, 1981)
The highly idealized problem of optimization of rheological properties of safety belts was formulated and solved by W. NACHBAR and J. B. SCIDPMOLDER [2]. In the present paper optimization is considered taking a more realistic description of an impact. The effect of plastic crushing of the front end of the car body is studied. The perturbation method is applied to obtain an effective solution, with the small parameter proportional to the length of the deformed front end of the vehicle. Two cases of total and partial crushing of the elements in the front of the passenger are distinguished under the assumption of constant average plastic resistance of the car body. Optimum viscoelastic properties of the safety belt are determined which maximize the initial "safe" speed of the vehicle before an impact.